ChemInform Abstract: Oxo‐Rhenium Catalyzed Reductive Coupling and Deoxygenation of Alcohols. Issue 41 (September 2016) - Kasner, Gabrielle R.; Boucher‐Jacobs, Camille; McClain, J. Michael II; Nicholas, Kenneth M.
Abstract: The rhenium‐catalyzed reaction of alcohol (I) with PPh3 leads to the dimeric hydrocarbon (II), whilst alcohols (III) and (V) give rise to deoxygenation products (IV) and (VI), respectively.